Social and Environmental Reporting and Auditing in Indonesia: Maintaining Organizational Legitimacy? - Basalamah, Anies S.; Jermias, Johnny (Gadjah Mada International Journal of Business, 2005)
The purpose of this study is to examine social and environmental reporting and auditing practices by companies in Indonesia. Consistent with our prediction, we found that social and environmental reporting and auditing are undertaken by management for strategic reasons, rather than on the basis of any perceived responsibilities. The results indicate that reporting and auditing social and environmental activities increases following threats to the companyâs legitimacy and ongoing survival. The results also support our prediction that social and environmental reports vary across companies. This study calls for mandatory reporting and auditing of social and environmental activities through regulations and reinforcements. This mandatory requirement is particularly needed for companies with activities that are considered socially and environmentally sensitive. Furthermore, this study reveals that the social and environmental reporting and auditing are performed by organizations other than accounting profession. We propose that accountants should partake in these activities given the expertise that they could usefully bring to these areas.